Co-expression of six tightly clustered odorant receptor genes in the antenna of the malaria mosquito Anopheles gambiae - Karner, Tim; Kellner, Isabelle; Schultze, Anna; Breer, Heinz; Krieger, Jürgen (Frontiers in Ecology and Evolution, 2015)
The behavior of female malaria mosquitoes, Anopheles gambiae, especially seeking out blood hosts or selecting oviposition sites, highly depends on the detection of relevant odorants by their sense of smell. This is mediated by olfactory sensory neurons (OSNs) which express distinct odorant receptor (OR) types. In the genome of A. gambiae 76 genes have been annotated to encode putative odorant receptors and the majority of these AgOR genes are arranged in clusters. To assess whether clustered AgOR genes are expressed in a characteristic manner we explored the topographic expression pattern of six tightly adjoined AgOR genes in the female antenna. Whole mount fluorescence in situ hybridization experiments were performed to visualize the olfactory neurons which express a distinct AgOR type in order to determine the number and the distribution of the cells. We found that within the thirteen antennal segments about 75 cells contain mRNA for the four receptor types AgOR13, AgOR15, AgOR17 and AgOR55. Moreover, about half of these cells also transcribe mRNA for the subtypes AgOR16 and AgOR47. Subsequent RT-PCR experiments with primer pairs spanning the coding regions of adjacent AgOR genes revealed the existence of polycistronic mRNA. This result indicates that individual genes were not transcribed but mRNA was comprised of coding sequence from several genes within the studied cluster. Taken together, the data indicate a unique principle for the expression of odorant receptor genes arranged in a large cluster and suggest that the corresponding olfactory neurons are endowed with a distinct set of odorant receptor types.